Extended and local structural characterization of a natural and 800 °C fired Na-montmorillonite–Patagonian bentonite by XRD and Al/Si XANES - Andrini, Leandro Rubén (2017)
A structural characterization of a Patagonian bentonite and its corresponding heating product (800 °C) was carried out. The nature of aluminum and silicon atoms was investigated using Al and Si K-XANES spectroscopy and compared with other well-known Al and/or Si containing materials. The studied material comes from Lago Pellegrini area-Rio Negro Province, Argentina. The main crystalline phase was confirmed to be a Na-montmorillonite. The thermal behavior was studied by DTA-TG-DTG and XRD. A Rietveld based quantification was performed as complementary study. About 90% Na-montmorillonite (clay mineral of smectite Group) content was confirmed and different impurities (quartz, gypsum and feldspars) were also quantified. The smectitic interlayer thermal displacement was determined between 15.49 and 9.81 Å. The XANES results allowed obtaining the AlIV/AlVI ratio and the local symmetry and distortions at Si and Al-sites. The tetra-coordination of silicon and the aluminumtetra and hexa-coordinatedwas found in both materials. The expected high AlIV/AlVI ratio was confirmed and pondered for the thermally treated bentonite.